2022
DOI: 10.3390/su14116484
|View full text |Cite
|
Sign up to set email alerts
|

Bench-Scale Fixed-Bed Column Study for the Removal of Dye-Contaminated Effluent Using Sewage-Sludge-Based Biochar

Abstract: Batik industrial effluent wastewater (BIE) contains toxic dyes that, if directly channeled into receiving water bodies without proper treatment, could pollute the aquatic ecosystem and, detrimentally, affect the health of people. This study is aimed at assessing the adsorptive efficacy of a novel low-cost sewage-sludge-based biochar (SSB), in removing color from batik industrial effluent (BIE). Sewage-sludge-based biochar (SSB) was synthesized through two stages, the first is raw-material gathering and prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…At pyrolysis temperatures and periods of 700 • C and 4 h, respectively, a high surface area of 431.82 m 2 /g and a pore volume of 0.134 cm 3 /g were reached in the initial screening analysis of Brilliant Blue R dye adsorption on various SSBs. In the study by Al-Mahbashi et al (2022), the effectiveness of the biochar made from sewage sludge was investigated to remove the color from wastewater used in batik in column trials. The results…”
Section: Adsorption Of Dyes In Industrial Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…At pyrolysis temperatures and periods of 700 • C and 4 h, respectively, a high surface area of 431.82 m 2 /g and a pore volume of 0.134 cm 3 /g were reached in the initial screening analysis of Brilliant Blue R dye adsorption on various SSBs. In the study by Al-Mahbashi et al (2022), the effectiveness of the biochar made from sewage sludge was investigated to remove the color from wastewater used in batik in column trials. The results…”
Section: Adsorption Of Dyes In Industrial Wastewatermentioning
confidence: 99%
“…In the study by Al‐Mahbashi et al. (2022), the effectiveness of the biochar made from sewage sludge was investigated to remove the color from wastewater used in batik in column trials. The results showed that biochar had a surface area of 117.7 m 2 /g, and that a maximum bed capacity of 42.30 mg/g was reached at a flow rate of 16 mL/h and a bed height of 12 cm.…”
Section: Industrial Applications For Environmental Remediationmentioning
confidence: 99%
“…For example, Birniwa and co-workers synthesized a polypyrrole-polyethyleneimine (PPy-PEI) adsorbent material with the aim of it being used for the removal of methylene blue dye from aqueous solutions [ 4 ]. Al-Mahbashi and co-workers studied a process to remove dyes used in batik production from industrial waters [ 5 ]. Another group of researchers, Al-dhawi and co-workers, studied the synthesis of a material that can extract boron from polluted waters [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption onto biochars derived from biomass is considered an effective and environmentally friendly method to remove many of the contaminants from wastewater [13][14][15]. Biochar can be produced from biomass using thermochemical and biochemical technologies.…”
Section: Introductionmentioning
confidence: 99%